Anti-termite curable composition

JP2025035491AActive Publication Date: 2025-03-13KOSHI PRESERVING
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023142555
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-13
Estimated Expiration
2043-09-01

AI Technical Summary

Benefits of technology

【0016】 本発明の防蟻用硬化性組成物によれば、無機物粒子がバインダー樹脂で固められることで防蟻層が形成され、当該防蟻層においては、隣り合う無機物粒子がバインダー樹脂により固められて一体化されるようになる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035491000001_ABST
    Figure 2025035491000001_ABST
Patent Text Reader

Abstract

To provide an improved novel anti-termite curable composition for reducing or eliminating problems caused by chemicals, while avoiding the high cost.SOLUTION: An anti-termite curable composition C is comprised by solidifying inorganic particles 1 with binder resin 2, and contains 60 mass% or more of inorganic particles with a particle size of 0.6 to 4.75 mm, out of the inorganic particles. It is preferable that the hardness measured by a Yamanaka soil hardness tester is 40 kg / cm2 or more and 150 kg / cm2 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an anti-termite hardenable composition suitable as an anti-termite means for applying to the surface of a building frame or structure. [Background technology]

[0002] Termites move underground from the outside of a building toward the basement inside the building, weaving their way into gaps and cracks in the concrete and eating away at building materials such as wooden supports and insulation, so various anti-termite measures have been developed.

[0003] A typical anti-termite measure is the application or spraying of an anti-termite agent, as shown in Patent Document 1. In this case, there are problems such as the smell of the anti-termite agent when performing anti-termite treatment again while living in the house after construction.

[0004] As shown in Patent Document 2, anti-termite treatments using natural materials such as Japanese cypress oil, wood vinegar, and liquid charcoal have been tried instead of anti-termite agents. Japanese cypress oil is extracted from Aomori Japanese cypress, a tree species that is resistant to termites, and wood vinegar is a liquid that is produced when making charcoal. Both have the effect of repelling insects. However, these natural materials have the disadvantages of being only effective to a limited extent, and being expensive compared to anti-termite agents, which are mass-produced chemical substances. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2007-331367 A [Patent Document 2] JP 2019-98724 A Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide, through extensive research, a new anti-termite hardenable composition which reduces or eliminates problems caused by chemicals while avoiding high costs. [Means for solving the problem]

[0007] [1] The present invention is characterized in that the anti-termite hardening composition is formed by solidifying inorganic particles with a binder resin.

[0008] [2] The second aspect of the present invention is the anti-termite hardenable composition according to [1], wherein the hardness measured by a Yamanaka soil hardness tester is 40 kg / cm 2 The present invention is characterized in that:

[0009] [3] The third invention relates to the anti-termite hardenable composition according to [1] or [2], wherein the hardness measured by a Yamanaka soil hardness tester is 150 kg / cm 2 The present invention is characterized in that:

[0010] [4] The fourth invention is characterized in that, in the anti-termite hardenable composition according to any one of [1] to [3], the inorganic particles have a particle size of 4.75 mm or less in 50 mass% or more.

[0011] [5] The fifth invention is characterized in that, in the anti-termite hardening composition according to any one of [1] to [4], the binder resin is blended in an amount of 15 parts by weight or more and 55 parts by weight or less per 100 parts by weight of the inorganic particles.

[0012] [6] A sixth aspect of the present invention is the anti-termite hardenable composition according to any one of [1] to [5], wherein the inorganic particles are converter slag.

[0013] [7] A seventh aspect of the present invention is the anti-termite hardenable composition according to any one of [1] to [6], wherein the binder resin is an acrylic resin.

[0014] [8] The eighth invention is characterized in that, in the anti-termite hardening composition according to [7], the acrylic resin is an acrylate ester styrene copolymer resin.

[0015] [9] The ninth invention is characterized in that, in the anti-termite hardenable composition according to any one of [1] to [8], a test specimen of the anti-termite hardenable composition having an X-direction length of 50 mm, a Y-direction length of 20 mm, and a Z-direction length of 32 mm, and having slits with a width and depth of 1 mm penetrating in the Y-direction at the center in the X-direction on each of the upper and lower surfaces, is subjected to a shear test in which a load is applied in the Z direction, where X is the left-right direction, Y is the front-back direction, and Z is the up-down direction, the load variation rate A (% / mm) per unit displacement (mm) from 8 mm to 12 mm in the Z-direction is in the range of -5 to 15. Effect of the Invention

[0016] According to the anti-termite curable composition of the present invention, an anti-termite layer is formed by solidifying inorganic particles with a binder resin, and in the anti-termite layer, adjacent inorganic particles are solidified and integrated by the binder resin.

[0017] In other words, the narrow gaps between adjacent inorganic particles are maintained by the binder resin, so that termites cannot pass through the narrow gaps between adjacent inorganic particles. In this way, the inorganic particle barrier and the adhesiveness of the binder resin combine to physically prevent termite intrusion.

[0018] As a result, for example, termite control is possible without using chemicals, and since the inorganic particles and binder resin can be mass-produced, problems associated with chemicals are eliminated or reduced, and no high costs are incurred, making it possible to provide a new and improved anti-termite hardenable composition. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a schematic diagram showing how termites cannot invade due to the anti-termite hardenable composition of the present invention. [Diagram 2] Schematic diagram showing the anti-termite performance test equipment [Diagram 3] Schematic diagram showing a hardness tester and a test specimen for hardness measurement [Figure 4] A perspective view showing a specimen used in a shear test. [Diagram 5] A graph showing an example of the results of a shear test: "Load L - Displacement H" DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, the anti-termite hardenable composition according to the present invention will be described in detail with reference to the drawings. However, the present invention is not limited to the illustrated examples, and can be practiced by making appropriate modifications within the scope of the above and below-mentioned aims, and all of them are included in the technical scope of the present invention.

[0021] [Curable composition for termite control] The anti-termite curable composition according to the present invention is composed of inorganic particles solidified with a binder resin. In one embodiment, the anti-termite curable composition as an anti-termite layer was developed by mixing converter slag, which is an example of inorganic particles, with acrylate ester styrene copolymer resin, which is an example of binder resin.

[0022] As shown in Fig. 1, the anti-termite curable composition C is capable of physically preventing the intrusion of termites t by combining the particle barrier of the converter slag 1 and the adhesiveness of the acrylate ester styrene copolymer resin 2. In addition, the high viscosity of the binder resin 2 imparts toughness to the anti-termite layer, making it difficult to break even when force is applied.

[0023] The hardened product formed by the anti-termite hardenable composition of the present invention does not crack even when subjected to external force, and can provide long-term and stable anti-termite properties to various building structures without the use of an anti-termite agent. The anti-termite hardenable composition of the present invention can be suitably used not only for newly built buildings, but also for the re-construction of aged buildings.

[0024] [Inorganic particles] One example of inorganic particles constituting the anti-termite hardening composition is converter slag (hereinafter simply referred to as "slag"). It is a by-product of converters used to manufacture steel from pig iron in steelworks, and is also called converter slag. The raw materials are all natural (iron ore, limestone, coke) and are produced at a high temperature of 1600°C, so it does not contain cadmium or arsenic, or if it does, it contains only trace amounts. Slag is hydraulic, meaning it hardens when it comes into contact with moisture, and it can expand the area where it can be anti-termite.

[0025] Inorganic matter is an inorganic compound composed of simple carbon compounds such as carbon dioxide and elements other than carbon such as water and metals, and is all substances other than organic matter. Slag is one type of steel slag, and depending on the type of furnace and the cooling method, steel slag includes blast furnace slag such as slowly cooled blast furnace slag and granulated blast furnace slag, and steelmaking slag such as converter slag and electric furnace slag, and each of these slags is also an inorganic particle. Slag may be used alone or in combination of two or more types.

[0026] The slag as inorganic particles used in the anti-termite hardening composition preferably contains 50% by mass or more of particles with a particle size of 4.75 mm or less, more preferably 60% by mass or more. A more suitable example is one containing 60% by mass or more of particles with a particle size of 0.6 mm or more and 4.75 mm or less. The reason is that if the particle size is larger than 4.75 mm, the gaps between the particles may become large and termites may be able to pass through, and if the particle size is smaller than 0.6 mm, there is a risk that the termites may carry the particles away.

[0027] For example, the slag may contain up to 20% particles with a particle size of less than 0.6 mm, with the remainder containing 60% or more by mass of particles with a particle size of 0.6 to 4.75 mm. Other examples include particles with a particle size of 1.18 mm to 4.75 mm or more by mass, particles with a particle size of 0.6 mm to 2.36 mm or more by mass, or particles with a particle size of 1.18 mm to 2.36 mm or more by mass. Furthermore, particles with a particle size of 4.75 mm or less may be contained at 70% or more by mass, or at 80% or more by mass.

[0028] As another example, the slag as inorganic particles used in the anti-termite hardening composition may contain 40% by mass or more of particles with a particle size of less than 0.6 mm. The small particle size and small gaps between the particles prevent termites from passing through, and the particles are bound with a binder resin having appropriate hardness and toughness, thereby preventing the termites from carrying them away. These inorganic particles with a particle size of less than 0.6 mm may be called "fine powder." The inorganic particles may contain 50 to 100% by mass of particles with a particle size of less than 0.6 mm, and preferably contain 60 to 95 or 100% by mass, and more preferably contain 70 to 95 or 100% by mass.

[0029] [Binder resin] Examples of binder resins that function as a curable liquid when mixed with a solvent include acrylic resins, and preferably acrylic ester-styrene copolymer resins. Acrylic resins are synthetic resins that have extremely high weather resistance and transparency, and their basic structure is a polymer of acrylic ester or methacrylic ester.

[0030] Acrylic resins include polymethylmethacrylate (PMMA), polyacrylic ester, sodium polyacrylate, polyacrylonitrile, polyacrylamide, acrylbutadiene, and others.

[0031] [About the mixture ratio] The blending ratio of inorganic particles such as slag and binder resin in the anti-termite curing composition C is preferably in the range of 15 parts by weight or more and 55 parts by weight or less per 100 parts by weight of inorganic particles. The reason is that if the binder resin is less than 15 parts by weight, the binder resin weakens the solidifying force of the inorganic particles, making the gaps between the inorganic particles easier to expand, and there is a risk that termites can pass through the gaps, and if the binder resin is more than 55 parts by weight, there is a risk that the binder resin will enter too much between the inorganic particles, expanding the gaps, and the termites will eat through the binder resin at the expanded gaps. It is preferable that the binder resin is in the range of 15 parts by weight or more and 45 parts by weight or less per 100 parts by weight of inorganic particles, and it is more preferable that the binder resin is in the range of 17 parts by weight or more and 42 parts by weight or less.

[0032] Various ratios are possible for the blending ratio of slag and binder resin in anti-termite hardening composition C using slag (hereinafter, slag A) containing 60 mass% or more of slag with a particle size of 0.6 mm or more and 4.75 mm or less, but in various tests described below, the ratio was 10 to 60 parts by weight of binder resin per 100 parts by weight of slag A. Note that the preferred blending ratio under these conditions is thought to be 30 to 40 parts by weight of binder resin, which is an intermediate range between 15 parts by weight and 55 parts by weight, per 100 parts by weight of slag A.

[0033] In the anti-termite hardening composition C, which uses slag (hereinafter referred to as slag B) containing 40 mass% or more of slag with a particle size of less than 0.6 mm, the compounding ratio of slag to binder resin was 20 to 60 weight parts of binder resin to 100 weight parts of slag B in the various tests described below.

[0034] [Various tests to evaluate performance] In order to measure the performance of the anti-termite hardening composition according to the present invention, an anti-termite test, a hardness measurement test, and a shear test were carried out. The contents of each test will be described below. The results of each test will be described later.

[0035] [Termite prevention test] As shown in FIG. 2, an anti-termite testing device B is prepared, which includes a hollow first case 3, a hollow second case 4, and a connecting pipe 5 that connects the first case 3 and the second case 4. The first case 3 is formed of a transparent or other cylindrical synthetic resin material that allows the inside to be seen through, with untreated soil 6 laid on the bottom and the top closed with an aluminum foil lid 7. The second case 4, like the first case 3, is formed of a transparent or other cylindrical synthetic resin material that allows the inside to be seen through, with untreated soil 8 laid on the bottom and the top closed with an aluminum foil lid 9, and a rectangular cedar sapwood 10 is placed on the untreated soil 8. The connecting pipe 5 is filled with an anti-termite hardening composition C, and is installed in a state of communication between the lower parts of the cases 3 and 4. The connecting pipe 5 is also preferably made of a transparent or other material that allows the inside to be seen through, but may be made of other materials.

[0036] The termite prevention test using this termite prevention test device B is carried out in a state where 300 termites t are placed in the first case 3 and the connecting pipe 5 is filled with test pieces c made of the anti-termite hardening composition C. In other words, this test is carried out to see whether the termites t can break through the test pieces c packed in the connecting pipe 5 and move to the second case 4 containing the cedar sapwood 10.

[0037] [Hardness measurement test] We measured the "hardness" of the anti-termite hardening composition C and investigated its relationship with the anti-termite effect. Specifically, we prepared a test specimen s (see FIG. 3) for hardness measurement test using the anti-termite hardening composition C, measured it using a hardness meter, and found a correlation between the presence or absence of anti-termite performance and the hardness to estimate the hardness range in which anti-termite performance is possible.

[0038] A standard or pocket-sized "Yamanaka soil hardness tester" was used as the hardness tester for measuring the hardness of the anti-termite hardening composition C. The Yamanaka soil hardness tester No. 351, manufactured by Fujiwara Seisakusho Co., Ltd., is an instrument for measuring soil hardness, one of the physical properties of soil, and can also be used for general soft materials other than soil. The general test method using the Yamanaka soil hardness tester is as follows.

[0039] [Hardness measurement test example] The method of measuring hardness using the Yamanaka soil hardness tester A will be described. As shown in FIG. 3, first, a flat cylindrical test specimen s with a diameter of 35 mm and a thickness of 10 mm is prepared from the anti-termite hardening composition C. Next, the cone 11 of the Yamanaka soil hardness tester A in a vertical position is placed on the horizontally placed test specimen s from above, and the Yamanaka soil hardness tester A is slowly pressed down until the flange 12 hits the test specimen s. Then, as an example, after pressing down 40 mm, the scale 13 of the Yamanaka soil hardness tester A is read, and the support strength is calculated from the stretching distance of the spring.

[0040] That is, when the cone 11 at the tip of the Yamanaka soil hardness tester A is pressed vertically into the flat cut cross section of the anti-termite hardening composition C, both the penetration depth of the cone 11 and the reaction force due to the compression of the spring of the Yamanaka soil hardness tester A at that time are measured simultaneously. Therefore, the support strength, that is, the hardness (unit: kg / cm) is calculated based on the penetration depth and the reaction force. 2 ) is calculated.

[0041] [Shear test] A specimen d (see FIG. 4) for a shear test is prepared using the anti-termite hardening composition C, and a shear test is performed using the specimen with a shear tester. A shear load is continuously applied to the specimen, and the load and displacement of the specimen are measured. Next, the specimen for the shear test and the shear test are described.

[0042] As shown in FIG. 4, when the left-right direction is X, the front-back direction is Y, and the up-down direction is Z, a rectangular test specimen d of the anti-termite hardening composition C is prepared, which has an X-direction length of 50 mm, a Y-direction length of 20 mm, and a Z-direction length of 32 mm, and has slits 14 with a width and depth of 1 mm formed in the center of the X-direction of the upper and lower surfaces, penetrating in the Y-direction. It is preferable that the upper and lower slits 14, 14 are formed by shifting the position to the left and right by the groove width of the slit 14 (1 mm) so as to face each other on the left-right center line P, but this is not limited. Then, a shear test was performed in which a load was applied in the Z direction along the left-right center line P of the test specimen d for the shear test (see FIG. 4), and the relationship between the load, which is the shear load, and the displacement was examined. The shear test machine is, for example, one used by the Japan Agricultural and Forestry Standards Association (JAS Association), more specifically, the Japan Agricultural and Forestry Standards for laminated lumber. EXAMPLES

[0043] [Example 1] The anti-termite hardening composition C of Example 1 has a compounding ratio of slag A and binder resin of 20 parts by weight to 100 parts by weight of slag A. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example 1 are designated c1, s1, and d1, respectively.

[0044] The results of the anti-termite test on the first test specimen c1 using the anti-termite test device B were, as shown in Table 1, a good result of 0 / 3 movement, when the number of tests was used as the denominator and the number of times that termites were able to invade from the first case 3 to the second case 4 was used as the numerator.

[0045] [Example 2] The anti-termite hardening composition C of Example 2 has a compounding ratio of slag A and binder resin of 30 parts by weight to 100 parts by weight of slag A. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example 2 are designated c2, s2, and d2, respectively.

[0046] The results of the anti-termite test of the second test specimen c2 using the anti-termite test device B were good, with 0 / 3 movement, as shown in Table 1.

[0047] [Example 3] The anti-termite hardening composition C of Example 3 has a compounding ratio of slag A and binder resin of 40 parts by weight to 100 parts by weight of slag A. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example 3 are designated c3, s3, and d3, respectively.

[0048] The results of the anti-termite test of the third test specimen c3 using the anti-termite test device B were good, with 0 / 3 movement, as shown in Table 1.

[0049] [Example 4] The anti-termite hardening composition C of Example 4 has a compounding ratio of 50 parts by weight of binder resin to 100 parts by weight of slag A. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example 4 are designated c4, s4, and d4, respectively.

[0050] The results of the anti-termite test of the fourth test specimen c4 using the anti-termite test device B were good, with 0 / 3 movement, as shown in Table 1.

[0051] [Example 5] The anti-termite hardening composition C of Example 5 has a compounding ratio of slag B and binder resin of 30 parts by weight to 100 parts by weight of slag B. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example 5 are designated c5, s5, and d5, respectively.

[0052] The results of the anti-termite test of the fifth test specimen c5 using the anti-termite test device B were good, with 0 / 3 movement, as shown in Table 1.

[0053] [Example 6] The anti-termite hardening composition C of Example 6 has a compounding ratio of 40 parts by weight of binder resin to 100 parts by weight of slag B. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example 6 are designated c6, s6, and d6, respectively.

[0054] The results of the anti-termite test of the sixth test specimen c6 using the anti-termite test device B were good, with 0 / 3 movement, as shown in Table 1.

[0055] [Example 7] The anti-termite hardening composition C of Example 7 has a compounding ratio of 50 parts by weight of binder resin to 100 parts by weight of slag B. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example 7 are designated c7, s7, and d7, respectively.

[0056] The results of the anti-termite test of the seventh test specimen c7 using the anti-termite test device B were good, with 0 / 3 movement, as shown in Table 1.

[0057] [Example a] The anti-termite hardening composition C of Example a has a compounding ratio of 10 parts by weight of binder resin to 100 parts by weight of slag A. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example a are ca, sa, and da, respectively.

[0058] The result of the anti-termite test of test specimen a ca using anti-termite test device B was 2 / 3 movement, as shown in Table 1.

[0059] [Example b] The anti-termite hardening composition C of Example b has a compounding ratio of slag A and binder resin of 60 parts by weight to 100 parts by weight of slag A. The test specimens for the anti-termite test, the hardness test, and the shear test of the anti-termite hardening composition C of Example b are designated cb, sb, and db, respectively.

[0060] The result of the anti-termite test of the test specimen b, cb, using the anti-termite test device B was 1 / 3 movement, as shown in Table 1.

[0061] [Example c] The anti-termite hardening composition C of Example c has a compounding ratio of slag B and binder resin of 20 parts by weight to 100 parts by weight of slag B. The test specimens for the anti-termite test, hardness test, and shear test of the anti-termite hardening composition C of Example c are designated cc, sc, and dc.

[0062] The result of the anti-termite test of test specimen c, cc, using anti-termite test device B was 2 / 3 movement, as shown in Table 1.

[0063] [Example d] The anti-termite hardening composition C of Example d has a compounding ratio of slag B and binder resin of 60 parts by weight to 100 parts by weight of slag B. The test specimens for the anti-termite test, the hardness test, and the shear test of the anti-termite hardening composition C of Example d are designated as cd, sd, and dd, respectively.

[0064] The result of the anti-termite test of test specimen d (cd) using anti-termite test device B was 1 / 3 movement, as shown in Table 1.

[0065] [Termite prevention test results] The results of the anti-termite test using the anti-termite test device B are shown in Table 1. The N number of specimens c1 to c7, ca to cd of Examples 1 to 7 and Examples a to d was 3, that is, three specimens were measured for each.

[0066] [Table 1]

[0067] As shown in Table 1, the termites t were sometimes able to break through the test specimens a to d ca to cd according to Examples a to d and enter the second case 4, but were unable to break through the test specimens c1 to c7 according to Examples 1 to 7 and move. In other words, in the anti-termite curable composition C using slag A, better anti-termite test results were obtained when the binder resin was in the range of 20 to 50 parts by weight, and in the anti-termite curable composition C using slag B, better anti-termite test results were obtained when the binder resin was in the range of 30 to 50 parts by weight. Therefore, the anti-termite curable composition C, which is made by solidifying inorganic particles with a binder resin, is able to provide anti-termite protection as a physical barrier without the use of chemicals, and it can be said that the anti-termite curable compositions C of Examples 1 to 7, in which the binder resin is blended in a range of 15 parts by weight or more and 55 parts by weight or less per 100 parts by weight of inorganic particles, provide even better anti-termite protection.

[0068] [Hardness measurement results] Table 2 shows the results of hardness measurement using the Yamanaka soil hardness meter A. A total of 11 types of test specimens s1 to s7 and sa to sd of Examples 1 to 7 and Examples a to d were used. Specimens s1-s7, a-d, s1-s7, sa-sd for the hardness test correspond to specimens c1-c7, ca-cd, ca-cd for the termite prevention test listed in Table 1, respectively, and each specimen was measured in triplicate, i.e., N number was 3.

[0069] [Table 2]

[0070] From the hardness measurement results shown in Table 2 and the anti-termite test results shown in Table 1, the following can be inferred. That is, in the anti-termite test results in Table 1, specimens 1 to 7, which are excellent products in which termites t could not move at all, and specimens c1 to c7 and ca to cd, which are good products in which termites t could hardly move, correspond to specimens s1 to s7 and a to d, and sa to sd, respectively, in Table 2, and show an average support strength of 44 kg / cm2 or more. On the other hand, specimens ca to cd, which are excellent products in which termites t could not move at all, correspond to specimens s1 to s7 and a to d, and sa to sd, respectively, in Table 2, and show an average support strength of 37 kg / cm2 or more. 2 The results are as follows. From these results, the hardness of the anti-termite hardenable composition C is 40 kg / cm as in Examples 1 to 7. 2 It is believed that if the above conditions are met, a more effective anti-termite effect will be achieved.

[0071] In the anti-termite hardenable composition C using slag B as inorganic particles 1, those containing 30 to 50 parts by weight of binder resin are very good, and those containing 20 and 60 parts by weight of binder resin are good, as shown in the test results in Tables 1 and 2. It is believed that a better anti-termite hardenable composition C can be constructed by mixing "23 parts by weight or more and 55 parts by weight or less of binder resin per 100 parts by weight of slag having a particle size of less than 0.6 mm." The compounding ratio of binder resin 2 in the anti-termite hardenable compositions C of Examples 1 to 4, which use slag with a relatively large particle size of 0.6 to 4.75, is 15 to 55 parts by weight, whereas the compounding ratio of binder resin 2 in the anti-termite hardenable compositions C of Examples 5 to 7, which use slag with a small particle size of less than 0.6, is 23 to 55 parts by weight, indicating that the lower limit is slightly shifted to the higher side.

[0072] [Shear test results] Specimens d for shear testing (see FIG. 4) were prepared as first to seventh specimens d1 to d7 for shear testing using the same anti-termite hardening compositions C as those in Examples 1 to 7 which obtained better results in both the anti-termite test results shown in Table 1 and the hardness measurement test results shown in Table 2. As a result of the shear testing, none of the seven specimens d1 to d7 broke even though the shear testing was continued until the displacement of the specimen reached 14 to 16 mm.

[0073] Fig. 5 shows an example of an LH graph, which is a load-displacement graph based on the shear test results, where L represents the load (unit: kgf) and H represents the displacement (unit: mm). The LH graphs based on the shear tests of each of the test specimens d1 to d7 show some variation in the load value itself, but all of them show the change curve shown in Fig. 5, that is, the change curve that does not lead to breakage. Therefore, it can be inferred that the anti-termite hardenable composition C based on each of the test specimens d1 to d7 according to Examples 1 to 7 has abundant toughness.

[0074] [Load fluctuation rate] The load variation rate was used as a means of evaluating each test piece d1 to d7 from the results of the shear test. The load variation rate R is given by: Formula (1): R = (nm) / m ÷ (12-8) × 100 (unit: % / mm) In other words, the load variation rate R per unit displacement of 1 mm is calculated by dividing the value (nm) of the load L required for the Z-direction displacement H to change from 8 mm to 12 mm by the value (m) of the load L when the displacement H is 8 mm, dividing the divided value (nm) / m by 4 mm (12 mm - 8 mm), and multiplying it by 100 (unit: % / mm). The load variation rates R of each specimen d1 to d7 calculated from the data obtained by the shear test are shown in Table 3.

[0075] [Table 3]

[0076] The load variation rate R (% / mm) of each of the test specimens d1 to d7 in the shear test of the anti-termite hardenable composition C according to Examples 1 to 7 was calculated, and it was found that all the load variation rates R were in the range of -5 to 15. From Fig. 5 and Table 3, in the shear test, the load variation rate R was in the low range of -5 to 15, that is, even if the amount of displacement increases, it does not break, and the load only increases or decreases slightly, and therefore it is considered that the anti-termite hardenable composition C has excellent toughness. Due to the excellent toughness, the anti-termite hardenable composition C does not crack even if there is a small earthquake, so there is no risk of termites invading through the cracks.

[0077] [About anti-termite effects] In the anti-termite hardening composition C, the state in which the slag particles 1 are closely arranged is maintained by being solidified by the binder resin 2. For example, as shown in FIG. 1, a configuration in which the binder resin 2 is filled into the gaps between the slag particles 1 and maintained is conceivable. The gaps between adjacent slag particles 1, 1 are very narrow and smaller than the size of the termites t. In addition, it is more preferable that the slag particles 1 contain 60% by mass or more of slag particles 1 with a size of 0.6 to 4.75 mm, or contain 40% by mass or more of slag particles less than 0.6 mm, and that the slag particles 1 are tightly adhered to each other and strongly held in position by the binder resin 2, so that the termites t cannot be removed.

[0078] 1, termites t that encounter the anti-termite hardening composition C cannot remove each particle 1, and cannot pass between adjacent particles 1, 1. In other words, the anti-termite effect is achieved by the synergistic action of the "particle barrier of the slag," "no gaps due to the adhesion of the binder resin," and "prevention of deformation due to the toughness of the anti-termite layer," which physically prevents the termites from advancing any further due to the anti-termite hardening composition C.

[0079] The above-mentioned anti-termite effect is effectively exhibited in the anti-termite hardening composition C which is composed of inorganic particles 1 bound with a binder resin 2. If the anti-termite hardening composition C is too hard, it becomes brittle and tends to lack toughness. Therefore, the hardness is set to 150 kg / cm 2 Therefore, the hardness of the anti-termite hardenable composition C is preferably 40 to 150 kg / cm 2 The range is preferably 50 to 130 kg / cm 2 A range of 50-100 kg / cm is preferable. 2 In addition, when the particle size of the slag is small, such as less than 0.6 mm, it is believed that an effective anti-termite effect is achieved through the synergistic effects of "no gaps due to the adhesion of the binder resin," "prevention of deformation due to the toughness of the anti-termite layer," and "moderate hardness of the binder resin."

[0080] The position-retaining power of the inorganic particles according to the present invention, i.e., the position-retaining action of the slag particles 1 due to being solidified with the binder resin 2, is clearly stronger than the position-retaining action due to the "self-hardening due to moisture", which is a property of slag. Therefore, the anti-termite hardening composition C exhibits a strong anti-termite effect due to the synergistic effect of the expansion of the anti-termite range due to the self-hardening of the slag particles 1 and the excellent position-retaining action of the slag particles due to the strong adhesion of the binder resin 2.

[0081] [Another Example] For example, the inorganic particles used in the anti-termite hardenable composition may contain 60 to 80 parts by weight of particles having a particle size of 1.4 to 2.8 mm so that termites cannot remove them and cannot pass through gaps. [Explanation of symbols]

[0082] 1. Inorganic particles: converter slag 2. Binder resin: Acrylic resin 14 Slit A Yamanaka type soil hardness tester C. Anti-termite hardenable composition R Load fluctuation rate t Termite

Claims

1. An anti-termite hardening composition comprising inorganic particles solidified with a binder resin.

2. The soil hardness measured by the Yamanaka soil hardness tester is 40 kg / cm 2 The anti-termite hardenable composition according to claim 1 .

3. The hardness measured by the Yamanaka soil hardness tester is 150 kg / cm 2 The anti-termite hardenable composition according to claim 2, which is as follows:

4. The anti-termite hardenable composition according to any one of claims 1 to 3, wherein the inorganic particles have a particle size of 4.75 mm or less in an amount of 50 mass % or more.

5. The anti-termite hardening composition according to any one of claims 1 to 3, wherein the binder resin is blended in an amount of 15 parts by weight or more and 55 parts by weight or less per 100 parts by weight of the inorganic particles.

6. The anti-termite hardenable composition according to any one of claims 1 to 3, wherein the inorganic particles are converter slag.

7. The anti-termite hardenable composition according to any one of claims 1 to 3, wherein the binder resin is an acrylic resin.

8. The anti-termite curable composition according to claim 7, wherein the acrylic resin is an acrylic acid ester-styrene copolymer resin.

9. The anti-termite hardenable composition according to any one of claims 1 to 3, wherein the anti-termite hardenable composition has a length in the X direction of 50 mm, a length in the Y direction of 20 mm, and a length in the Z direction of 32 mm, and has slits with a width and depth of 1 mm penetrating in the Y direction at the center in the X direction on each of the upper and lower surfaces, and when a shear test is performed in which a load is applied in the Z direction, the load variation rate A (% / mm) per unit displacement (mm) from 8 mm to 12 mm in the Z direction is in the range of -5 to 15.

Citation Information

Patent Citations

  • Artificial water bottom base

    JP2006288323A

  • Insect-proof structure of building

    JP2008121200A

  • Sealant for building

    JP2015231969A

  • Ant-proof curable composition

    JP2022176634A

  • Method for impregnating lumber with chemical

    JP2007331367A